Dr. Vanek Šiftar - prvi zaslužni profesor prava na Univerzi v Mariboru: Spominska publikacija ob 65-letnici študija prava v Mariboru - Hojnik, Janja (University of Maribor Press, 2025)
Vanek Šiftar, First Professor Emeritus of Law at University of Maribor: Commemorative Publication on the 65th Anniversary of Legal Education in Maribor. The publication presents the life of Prekmurje-born law professor Ivan Vanek Šiftar, who worked during a time when there was no public discourse about judicial independence or university autonomy. He served both in the judiciary and in academia, operating under party oversight, yet consistently striving to uphold professional expertise over political motives in both spheres. He believed that only knowledge could improve the living standards of people living on the geographical periphery of Slovenia. Throughout his career, he served as a prosecutor, judge, member of parliament, and law professor. He also acted as the second director of the Higher Law School in Maribor, at a time when the school’s very existence was far from secure. After his retirement, he was named the first professor emeritus of law at the University of Maribor.